A Task Analysis of Client Re‐engagement: Therapeutic De‐escalation of High‐Conflict Coparents. Issue 4 (12th December 2019) - Anderson, Shayne R.; Sumner, Brock W.; Parady, Andrea; Whiting, Jason; Tambling, Rachel
Abstract : Parents who are engaged in protracted conflict following a divorce are often referred to coparenting therapy. Episodes of intense conflict are common during these therapy sessions and often result in coparents disengaging from the therapist while they engage in escalating conflict with each other, potentially disrupting their progress in therapy. The purpose of this study was to identify how therapists successfully re‐engage clients in the session. To understand this process, 24 disengagement events (12 successful and 12 unsuccessful) from 13 cases were analyzed using a task analytic approach. The sample included coparent dyads referred by the judicial system to a high‐conflict coparenting therapy program. Task analysis was used to create a model of how re‐engagement unfolds in treatment. The empirical model that resulted has five phases: (1) disengagement from the therapeutic process, (2) disruption of the conflict, (3) de‐escalating the most escalated coparent, (4) de‐escalating the other coparent, and (5) therapist buffered re‐engagement. Successful episodes of re‐engagement tended to have therapists who remained active throughout the conflict episode, used structuring interventions aimed at disrupting and then regulating the most escalated partner, blocked attempts to re‐engage in conflict, and then repeated this process with the less escalated partner. Additional interventions that promote therapeutic re‐engagement are described for each phase, and implications for clinicians and researchers are discussed. Abstract : Los padres que participan en un conflicto extendido después de un divorcio generalmente son derivados a terapia para la cocrianza de los hijos. Durante estas sesiones de terapia, son comunes los episodios de conflicto intenso entre los padres, quienes, como resultado, generalmente se distancian del terapeuta mientras participan en una escalada de conflictos entre sí que tiende a interrumpir su avance en la terapia. El propósito de este estudio fue identificar cómo los terapeutas reincorporan satisfactoriamente a los pacientes en la sesión. Para comprender este proceso, se analizaron 24 situaciones de distanciamiento (12 satisfactorias y 12 insatisfactorias) de 13 casos utilizando un método analítico de tareas. La muestra incluyó díadas de compañeros de crianza derivados por el sistema judicial a un programa de terapia para la cocrianza con un alto grado de conflicto. Se utilizó el análisis de tareas para crear un modelo de cómo se desarrolla la reincorporación en el tratamiento. El modelo empírico que resultó tiene cinco fases: 1) distanciamiento del proceso terapéutico, 2) interrupción del conflicto, 3) sosiego del compañero de crianza que más escaló, 4) sosiego del otro compañero de crianza, y 5) reincorporación reforzada por el terapeuta. Los episodios satisfactorios de reincorporación tendieron a tener terapeutas que permanecieron activos durante el episodio de conflicto, utilizaron intervenciones de estructuración orientadas a la interrupción y luego a la regulación al compañero de crianza que más escaló, bloquearon los intentos de reactivar el conflicto y luego repitieron este proceso con el compañero de crianza que menos escaló. Se describen otras intervenciones que promueven la reincorporación terapéutica en cada fase y las implicancias para los clínicos y los investigadores. Abstract : 离婚后那些陷入持久冲突中的孩子的父母们往往得到建议去接受父母共同抚养孩子的治疗。在治疗过程中，父母双方频发激烈冲突的情况，通常会导致不能跟治疗师合作。他们之间的冲突逐步升级也有可能破坏他们的治疗进度。本研究旨在确定治疗师如何成功地重新让病人参与到合作治疗中来。为了了解此过程，本研究使用任务分析方法，就13个案例中的24个不合作事件（12个成功案例和12个失败案例）进行分析。样本包括司法系统转介给高冲突父母共同疗法计划的成对父母。本研究使用了任务分析用于创建一个模型，以此模型来展现让病人重新参与合作在治疗中是如何具体发挥作用的。分析结果得出的经验模型包括以下五个阶段：1）治疗过程中断; 2）阻止破坏继续发生； 3）缓解冲突激烈程度最大的合作养育的一方； 4）缓解冲突中的另一方的情绪； 5）治疗师缓冲后双方重新参与到治疗中来。病人重新参与到治疗过程的成功案例中，治疗师往往在整个冲突期间保持活跃，积极使用结构性干预措施来制止冲突，然后调节激烈程度升级幅度大的一方，阻止他们重新引发冲突的尝试，然后与冲突激烈程度较小的另一方重复该过程。每个阶段都介绍了促进治疗性重新参与的其他干预措施，并讨论了对临床医生和研究人员的意义。